Annular pancreas with duodenal obstruction- case report and review of literatures - Rahman, M A Mushfiqur; Bhuiyan, Md Akbar Husain; Sajid, Md Minhajuddin; Hasan , Muhammed Anamul; Das, Sahadeb Kumar (Journal of Paediatric Surgeons of Bangladesh, 2018)
Annular pancreas as a cause of extrinsic duodenal obstruction is rare; with estimated incidence of one in 12,000-15,000 live births. Age of presentation varies due to differences in severity of symptoms of upper gastrointestinal tract obstruction. The band of pancreatic tissue encircling the 2nd part of Duodenum is responsible for narrowing of duodenal luminal diameter which subsequently determines the degree of obstruction. Various methods of bypassing the constriction without injuring the pancreatic tissue, are available; of them diamond shaped duodeno- duodenostomy as described by Kimura is widely practiced. The surgical outcome is satisfactory if there are no associated risk factors like prematurity, low birth weight, sepsis and other congenital anomalies. We have treated only three cases in last five years from January, 2011 to December, 2015. Two of them were neonate with acute presentation and one aged five and half years with chronic symptoms. Diamond shaped duodeno-duodenostomy was done in all patients. One of the neonate expired postoperatively due to sepsis and rest of the two had uneventful surgical recovery. Journal of Paediatric Surgeons of Bangladesh (2016) Vol. 7 (1): 22-25